2022
DOI: 10.3390/microorganisms10051070
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing Reveals Multiple Subpopulations of Dominant and Persistent Lineage I Isolates of Listeria monocytogenes in Two Meat Processing Facilities during 2011–2015

Abstract: Listeria monocytogenes is a foodborne pathogen with a highly clonal population structure comprising multiple phylogenetic sub-groups that can persist within food processing environments and contaminate food. The epidemiology of L. monocytogenes is well-described in some developed countries; however, little is known about the prevalence and population structure of this pathogen in food and food processing environments located in less developed regions. The aim of this study was to determine the genetic characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 78 publications
1
2
0
Order By: Relevance
“…Other authors also reported similar results [ 21 , 27 , 52 , 53 ] with hypervirulent clones such as CC1, CC2 and CC6 persisting for long time. These findings could indicate that the fitness of a strain is relative to the environment with which it is interacting.…”
Section: Discussionsupporting
confidence: 69%
“…Other authors also reported similar results [ 21 , 27 , 52 , 53 ] with hypervirulent clones such as CC1, CC2 and CC6 persisting for long time. These findings could indicate that the fitness of a strain is relative to the environment with which it is interacting.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, using WGS, Demaître et al (2021) concluded that the persistence of Listeria contamination on the slaughter line was due to the presence of hypovirulent lineage II CC9 strain in the carcass splitter for longer than one year. However, Burnett et al (2022) found hypervirulent I strains of L monocytogenes in two meat processing facilities during 2011-2015. These strains originated from raw and environmental samples, representing serotypes 4b, 1/2b and 3b and belonged to clonal complexes: CC1, CC2, CC5 and CC288.…”
Section: Transmission Routes and Wgsmentioning
confidence: 99%
“…(A) Genetic lineage I CC associated with environmental persistence; (B) Genetic lineage II CC associated with environmental persistence. Note : Based on (Brown et al., 2021; Burnett et al., 2022; Centorotola et al., 2021; Chase et al., 2017; Chen et al., 2017; Chen et al., 2022; Chen, Burall, et al., 2016; Cherifi et al., 2018; Chiara et al., 2014; Conficoni et al., 2016; Corcoran et al., 2013; Daeschel et al., 2022; De Cesare et al., 2017; Demaitre et al., 2021; Demaître et al., 2021; Elson et al., 2019; Fagerlund et al., 2016; Fagerlund et al., 2020; Fei et al., 2015; Gan et al., 2021; Gelbicova et al., 2018; Gelbícová et al., 2019; Guidi et al., 2021; Guidi et al., 2022; Harrand et al., 2020; Holch et al., 2013; Hurley et al., 2019; Jensen et al., 2016; Kaszoni‐Rückerl et al., 2020; Knudsen et al., 2017; Kovacevic et al., 2016; Lachmann et al., 2021; Lachmann et al., 2022; Lake et al., 2021; Lassen et al., 2016; Lee et al., 2019; Liu et al., 2022; Louha et al., 2020; Lu et al., 2019; Luth et al., 2020; Madden et al., 2018; Maggio et al., 2021; Maurella et al., 2018; McLauchlin et al., 2020; Melero, Manso, et al., 2019; Melero, Stessl, et al., 2019; Mohan et al., 2021; Moretro et al., 2017; Muhterem‐Uyar et al., 2018; Negrete et al., 2022; Nilsson et al., 2012; Nowak et al., 2017; Nowak et al., 2021; Nüesch‐Inderbinen et al., …”
Section: Assessmentmentioning
confidence: 99%